Pesquisa de Streptococcus Agalactiae em gestantes residentes em Belém-Pará - RIBEIRO, Kleber Dias (Universidade Federal do Pará, 2013)
In the Steptococus agalactiaie infections in newly born two forms are recognized, that of precocious beginning, whose clinical picture is characterized by bacteremia with lung involvement, meningitis, septic shock and neutropenia, and the of late beginning, where the bacteremia associated to the meningitis is the predominant clinical manifestation. Being considered the gravity of the pathology, the absence of information about the incidence of this bacterium in resident pregnant women in the north area of Brazil and the importance of diagnosis, is fundamental the determination of the occurrence of the estreptococos of the group B in this population. Therefore, this study aimed the laboratorial diagnosis of streptocuccus agalactiae in the pregnant women feminine genital treat, in the last quarter of gestation, determining the incidence and alerting about the importance of the diagnosis in the prenatal exam. This study was realized in the period of February to August of 2002, in 50 pregnant women resident and domiciled in the city of Belem-Para, coming from the section of gynecology of the Federal University of Para. The bacteria identification carry out through the bacterioscopy and culture of the vaginal contents. Of the 50 studied pregnant women, seven (14%) presented positive culture for Streptococcus agalactiae. Of these, two (28,6%) were first gestation and five (71,4%) second gestation. This results to indication the significant presence of the bacterium, indicating the need of the adoption procedures for prevention of the infection by this agent, due the high index morbidade and mortality associated to the estreptococo of the group B.